2023
DOI: 10.3390/life13061379
|View full text |Cite
|
Sign up to set email alerts
|

10-Year Risk for Cardiovascular Disease Associated with COMISA (Co-Morbid Insomnia and Sleep Apnea) in Hypertensive Subjects

Laura Draelants,
Camille Point,
Benjamin Wacquier
et al.

Abstract: Due to the few studies available, this study aimed to investigate the 10-year risk for cardiovascular disease (CVD) associated with COMISA (co-morbid insomnia and sleep apnea) in hypertensive subjects. Clinical data of 1009 hypertensive subjects extracted from the Sleep Laboratory database were analyzed. Framingham Risk Score ≥ 10% was used as a cut-off to identify hypertensive subjects with high 10-year risk for CVD. The association between 10-year risk for CVD and COMISA was investigated using logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…Consistent with the data currently available in the literature, we confirmed that ID (67.0%) and OSAS (42.0%) are frequent comorbidities for MDD patients [44,45]. Furthermore, in this study, we demonstrated that 58.4% of MDD patients with OSAS presented a comorbid ID, which seems to indicate a more frequent occurrence of insomnia complaints in cases of OSAS for MDD patients than for the other subpopulations currently studied for COMISA [12,13,18]. Furthermore, similar to other available studies [12,13,18], we demonstrated that high 10-year cardiovascular risk was significantly associated with COMISA but was not significantly associated with ID or OSAS alone.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with the data currently available in the literature, we confirmed that ID (67.0%) and OSAS (42.0%) are frequent comorbidities for MDD patients [44,45]. Furthermore, in this study, we demonstrated that 58.4% of MDD patients with OSAS presented a comorbid ID, which seems to indicate a more frequent occurrence of insomnia complaints in cases of OSAS for MDD patients than for the other subpopulations currently studied for COMISA [12,13,18]. Furthermore, similar to other available studies [12,13,18], we demonstrated that high 10-year cardiovascular risk was significantly associated with COMISA but was not significantly associated with ID or OSAS alone.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in this study, we demonstrated that 58.4% of MDD patients with OSAS presented a comorbid ID, which seems to indicate a more frequent occurrence of insomnia complaints in cases of OSAS for MDD patients than for the other subpopulations currently studied for COMISA [12,13,18]. Furthermore, similar to other available studies [12,13,18], we demonstrated that high 10-year cardiovascular risk was significantly associated with COMISA but was not significantly associated with ID or OSAS alone. However, pathophysiologically, this high prevalence of COMISA and its potential role in unfavorable cardiovascular prognosis for MDD patients may be explained by different elements.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations